EXPLORING THE INTERSECTION OF PSYCHOLOGY AND EFFECTIVE TEACHING METHODS IN PRESCHOOL EDUCATION - Adilbekova Manzura Usenbek qızı (Journals Park Publishing, 2023)
Preschool education plays a pivotal role in laying the foundation for a child's cognitive, social, and emotional development. Understanding the principles of psychology can greatly enhance the effectiveness of teaching methods employed in preschool settings. In this article, we will delve into the key psychological factors influencing preschool children and explore how educators can leverage this knowledge to create a stimulating and supportive learning environment.
Keywords: Preschool education, Psychology, Teaching methods, Cognitive development, Social and emotional development, Behavioral psychology, Vygotsky's sociocultural theory, Individual differences, Executive function.